A process-genre approach with genAI Feedback: Interpersonal lexicogrammar development - Zainurrahman, Zainurrahman; Emilia, Emi; Rodliyah, Rojab Siti (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
A genre-based approach is argued to be effective in developing students’ academic writing ability, but feedback provision remains a challenge. Studies on GenAI feedback have shown that GenAI tools can provide students with immediate, personalized feedback. However, a few studies have investigated the impact of integrating GenAI feedback into a genre-based approach. To fill this gap, this study integrated GenAI feedback into a process-genre approach (PGA) to teaching exposition, which is an academic genre. Focusing on students’ interpersonal lexicogrammatical developmental trajectory, this study employed a single-case study design. Data were collected from 15 EFL (English as a foreign language) undergraduate students' drafts (diagnostic writing test, four successive drafts, and final writing test). Students’ texts were scored using an SFL-informed rubric. The developmental trajectory was analyzed using repeated-measures ANOVA, along with the SFL mood, modality, and appraisal systems. The results indicated a statistically significant increment in students’ interpersonal grammar, F(2.85, 39.92) = 33.56, p < .001, ηp2 = .706, though a slight drop in the final writing test was observed. This study concludes that PGA with GenAI feedback could facilitate students’ interpersonal lexicogrammar, but students still needed learning and writing support from the teacher. The findings of this study contribute to our understanding of the PGA with GenAI feedback in teaching exposition.